Molecular precursor derived SiBCN/CNT and SiOC/CNT composite nanowires for energy based applications - Bhandavat, Romil (Kansas State University, 2013)
Molecular precursor derived ceramics (also known as polymer-derived ceramics or PDCs) are high temperature glasses that have been studied for applications involving operation at elevated temperatures. Prepared from controlled thermal degradation of liquid-phase organosilicon precursors, these ceramics offer remarkable engineering properties such as resistance to crystallization up to 1400 °C, semiconductor behavior at high temperatures and intense photoluminescence. These properties are a direct result of their covalent bonded amorphous network and free (-sp2) carbon along with mixed Si/B/C/N/O bonds, which otherwise can not be obtained through conventional ceramic processing techniques. This thesis demonstrates synthesis of a unique core/shell type nanowire structure involving either siliconboroncarbonitride (SiBCN) or siliconoxycarbide (SiOC) as the shell with carbon nanotube (CNT) acting as the core. This was made possible by liquid phase functionalization of CNT surfaces with respective polymeric precursor (e.g., home-made boron-modified polyureamethylvinylsilazane for SiBCN/CNT and commercially obtained polysiloxane for SiOC/CNT), followed by controlled pyrolysis in inert conditions. This unique architecture has several benefits such as high temperature oxidation resistance (provided by the ceramic shell), improved electrical conductivity and mechanical toughness (attributed to the CNT core) that allowed us to explore its use in energy conversion and storage devices. The first application involved use of SiBCN/CNT composite as a high temperature radiation absorbant material for laser thermal calorimeter. SiBCN/CNT spray coatings on copper substrate were exposed to high energy laser beams (continuous wave at 10.6 μm, 2.5 kW CO2 laser, 10 seconds) and resulting change in its microstructure was studied ex-situ. With the aid of multiple techniques we ascertained the thermal damage resistance to be 15 kW/cm2 with optical absorbance exceeding 97 %. This represents one order of magnitude improvement over bare CNTs (1.4 kW/cm2) coatings and two orders of magnitude over the conventional carbon paint (0.1 kW/cm2) currently in use. The second application involved use of SiBCN/CNT and SiOC/CNT composite coatings as energy storage (anode) material in a Li-ion rechargeable battery. Anode coatings (~1mg/cm2) prepared using SiBCN/CNT synthesized at 1100 °C exhibited high reversible (useable) capacity of 412 mAh/g even after 30 cycles. Further improvement in reversible capacity was obtained for SiOC/CNT coatings with 686 mAh/g at 40 cycles and approximately 99.6 % cyclic efficiency. Further, post cycling imaging of dissembled cells indicated good mechanical stability of these anodes and formation of a stable passivating layer necessary for long term cycling of the cell. This improved performance was collectively attributed to the amorphous ceramic shell that offered Li storage sites and the CNT core that provided the required mechanical strength against volume changes associated with repeated Li-cycling. This novel approach for synthesis of PDC nanocomposites and its application based testing offers a starting point to carry out further research with a variety of PDC chemistries at both fundamental and applied levels.
Keywords: Polymer derived ceramics; Carbon nanotubes; Nanocomposites; Lithium ion battery; Laser calorimeter; Core-shell nanowires; Materials Science (0794)